2014
DOI: 10.1111/acps.12332
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide in schizophrenia: systematic review and clinical recommendations

Abstract: Identification of risk factors for suicide in individuals diagnosed with schizophrenia is imperative to improve clinical management and develop strategies to reduce the incidence of suicide in this population. This study provides the critical overview of available data and clinical recommendations on recognition and management of the above-mentioned risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 83 publications
3
87
1
6
Order By: Relevance
“…These findings are in line with findings from non-European countries where second-generation Latinos where found to attempt suicide more than first-generation Latinos. Researchers suggested that it might be due to acculturative stress [9]. This raises the following questions: do second-generation immigrants experience higher levels of acculturative stress than first generation immigrants?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are in line with findings from non-European countries where second-generation Latinos where found to attempt suicide more than first-generation Latinos. Researchers suggested that it might be due to acculturative stress [9]. This raises the following questions: do second-generation immigrants experience higher levels of acculturative stress than first generation immigrants?…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that immigration may act as a risk factor for suicide [8,9]. Other studies have suggested that immigration might act as a protective factor against suicide [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although suicide has a role in the shorter life expectancy [2], a large proportion of the early deaths are the result of cardiovascular disease (CVD) [3]. In comparison with the general population, the deaths of more than two-thirds of schizophrenia patients are the result of CVD [4].…”
Section: Introductionmentioning
confidence: 99%